On Attitudes towards Language - Miketić Subotić, Sanja D. (Sociološki pregled, 2024)
The aim of the paper is to present theoretical observations about attitudes towards language through the prism of social psychology and from a sociolinguistic point of view by reviewing the basic terms, perspectives, and research of theoretical and methodological significance for this area of sociolinguistics. At the same time, we will present their usual methodological framework and the importance of research.